Protective effects of extracts from Acer truncatum leaves on SLS-induced HaCaT cells - Fan, Yanxiao; Gu, Ronghui; Zhang, Ruifei; Wang, Miaomiao; Xu, Heran; Wang, Min; Long, Chunlin (Frontiers in Pharmacology, 2023)
Acer truncatum Bunge (Sapindaceae or formerly Aceraceae) is a tall deciduous tree native to China. Traditionally, the leaves of A. truncatum are decocted and used by Chinese Mongolians, Koreans, and Tibetans to treat skin itching, dry cracks, and other skin ailments, which indicates A. truncatum leaves may have a potential inhibitory effect on various skin inflammations. To examine the protective effect against skin inflammations of A. truncatum leaf extract (ATLE), an in vitro dermatitis model was established using sodium dodecyl sulfate (SLS)-induced HaCaT cells. The anti-inflammatory effect of ATLE was evaluated by analyzing cell viability, apoptosis, reactive oxygen species (ROS), interleukin 6 (IL-6), and prostaglandin E2 (PGE2) levels. Orthogonal experiments showed that the pretreatment with ATLE can reduce the IL-6 levels, PGE2 levels, and apoptosis increased in SLS-stimulated HaCaT cells, which indicates that ATLE has positive efficacy for dermatitis. Furthermore, three flavonoid compounds kaempferol-3-O-α-L-rhamnoside, quercetin-3-O-α-L-rhamnopyranoside, kaempferol-3,7-di-O-α-L-rhamnoside, and 1,2,3,4,6-Penta-O-galloyl-β-D-glucopyranose (PGG) were isolated and identified. Among them, kaempferol-3,7-di-O-α-L-rhamnoside was isolated from this plant for the first time. These compounds have been proven to have an anti-inflammatory effect. They may contribute to the efficacy of A. truncatum in treating skin inflammation. The results revealed that ATLE has the potential to be used as an additive in various skin care products to prevent skin inflammations and may be incorporated in formulations for topical application as a therapeutic approach to dermatitis.